Prevalence of Diabetes Mellitus and its Associated Factors among Adults in Malaysia: Findings from the National Health and Morbidity Survey 2019 - Ismail, Hasimah; Saminathan, Thamil Arasu; Robert Lourdes, Tania Gayle; Rodzlan Hasani, Wan Shakira; Ab Majid, Nur Liana; Mohd Yusoff, Muhammad Fadhli (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Diabetes mellitus (DM) is a major non-communicable health problem in both developed and developing countries, including Malaysia. This study aimed to determine the prevalence of DM and identify associated factors among adults in Malaysia. MATERIALS AND METHODS: A nationwide cross-sectional study was conducted in 2019 involving 10,464 respondents. A two-stage stratified sampling design was employed to select a representative sample of adults aged ≥18 years. Data was collected using structured and validated questionnaires administered through face-to-face interviews. Finger-prick fasting blood glucose tests were performed on respondents without a known DM diagnosis. All analyses were weighted to represent the Malaysian adult population. Chi-square tests and multiple logistic regression analyses were used to determine the associations between DM and the associated factors, with a significance level set at 0.05. RESULTS: The overall weighted prevalence of DM was 18.3% (n=2629). Higher prevalence was observed among individuals aged ≥60 years (41.5%), of Indian ethnicity (31.4%), physically inactive individuals (22.5%), obese individuals (27.1%), those with hypertension (36.0%), and those with high cholesterol levels (30.4%). Logistic regression identified age, ethnicity, obesity, hypertension, and cholesterol levels as significant factors associated with DM. CONCLUSION: The prevalence of DM among Malaysian adults remains high. Targeted strategies focusing on high-risk groups, particularly older adults, individuals of Indian ethnicity, those with obesity, hypertension, and dyslipidaemia, are important to reduce the national diabetes burden.